Hukuman Kebiri Bagi Kejahatan Pedophilia - Putri Situmeang; Adi Syahputra Sirait (Jurnal El-Thawalib, 2021)
Pedophilia is a form of sexual violence against children. This crime is an extraordinary crime because it violates the honor and threatens the life of the child as the successor of the nation's ideals. Various efforts have been made by the government to provide protection for children, from increasing penalties and fines to stipulating chemical castration as a sanction for action. In jinayah fiqh itself, castration as a criminal sanction is not known in Islamic law, so it raises a lot of pros and cons in various circles of society, especially scholars regarding the emergence of castration punishment in criminal sanctions for child protection. The formulation of the problem from this research is what are the dimensions of fiqh jinayah in the  Law Number 17 of 2016 concerning the castration penalty for pedophilia crimes. The purpose of this study is to determine the dimensions of fiqh jinayah in the RI Law Number 17 of 2016 concerning the castration penalty for pedophilia crimes. Furthermore, the type of research used is the type of empirical normative research, using a conceptual approach. The results obtained, that in the determination of castration for the crime of pedophilia in the  Law Number 17 of 2016 there are dimensions of fiqh jinayah which are viewed from the perspective of maqashid al-syariah and maslahah al-mursalah. In the castration punishment in the perspective of maqashid al-syariah, there is a goal of passing down the shari'a that is oriented towards the maintenance of al-kulliyat al-khamsah, namely hifz ad-din, hifz an-nafs, hifz al-'aql, hifz an-nasb and hifz al-mal, In addition to maqashidal-syariah, there is also benefit as God's goal in lowering the Shari'a, namely maslahah al-mursalah, the form of the existence of maslahah in castration punishment in the form of jalb al-manafi and dar al-mafasid at the al-hajiyyat (secondary) level. With the fulfillment of the fiqh dimensions of jinayah in the castration punishment, it shows the purpose and spirit of Islam in legal legislation, because it contains the maintenance of maqashid al-khamsah and also benefits.